The conflict between data and perception in placement reform and acceleration of English coursework - Wild, Corbyn Marie (Kansas State University, 2022)
This work studied an institution’s experiences with acceleration and placement reform in English coursework as changes in these measures affected student persistence, completion, and subject mastery in English composition. Through assessing student learning outcomes after placement reform and acceleration, this study compared students’ success through institutional data with the perceptions of their success among faculty and counselors. Perceptions were gathered through a Likert-scale survey coupled with thematically coded open-ended questions that reveal an innate desire for increased agency in the implementation of new initiatives. For practitioners, this study provides further insight into placement reform and the acceleration of English in a real-world context with suggestions for increased engagement from faculty and staff when implementing new initiatives. Ultimately, this study found far reaching implications for practice that include consistently gauging the perception of faculty and counselors, transparently clarifying processes and data, establishing a best-practice assessment plan, and developing a shared understanding of student success.
Keywords: English composition; Acceleration; Placement reform; Student learning outcome assessment; Student success; Perception